Sedentary Behavior Of Elementary School Students Based On Class Teacher Perceptions And Physical Education Teacher, Sports And Health In The District Turen - Sugianto, Irgi; Ernata, Yusvidha; Dwi Saputro, Yulianto (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This type of quantitative research using a comparative causal method was carried out by comparing the perceptions of class teachers and PJOK teachers to determine the sedentary behavior of elementary school students spread across Turen District. Data was collected via an online questionnaire/questionnaire (google form) with 5 Likert answer scales and analyzed using a single mean versus criterion test (one sample t-test) and an independent group mean difference test (independent sample t-test). IBM SPSS Statistics 25 is used to make it easier to calculate analysis results. The findings of this research are (1) The physical activity of elementary school children according to the class teacher has not met the adequate criteria set, (2) The physical activity of elementary school children according to the PJOK teacher has not met the adequate criteria set, and (3) There is no significant difference in mean. between the class teacher's perception and the PJOK teacher's perception of the sedentary behavior of elementary school age children.